Simulating water and salt changes in the root zone of salt–alkali fragrant pear and the selection of the optimal surface drip irrigation mode - Li, Yanjie; Gong, Ping; He, Xinlin; Liu, Hongguang; Li, Zhijie; Li, Ling; Wang, Chunxia; Xu, Qiang; Chen, Quan; Wei, Jie; Lin, Ping; Yu, Xuyong (Frontiers in Plant Science, 2024)
Fruit Trees and the Selection of the Optimal Surface Drip Irrigation Mode. The study only focuses on two years of Fragrant Pear trees, and there are certain differences in various indicators among different fruit trees. It is recommended that the title be specific to the target crop.We greatly appreciate your professional comments on our article. We have revised the title to "Simulating Water and Salt Changes in the Root zone of Salt-Alkali Fragrant Pear and the Selection of the Optimal Surface Drip Irrigation Mode".